Analysis of the oil and petroleum market in Ukraine - Vaschenko, V. (Land Management, Cadastre and Land Monitoring, 2018)
Abstract. Today, the issues of oil and petroleum products are very important both in the theoretical and practical aspects. Of particular importance is the issue of completeness and compliance with the current market conditions of the existing in Ukraine order of formation of prices for petroleum domestic production. The article analyzes the current state of the oil market in Ukraine. The dynamics of average prices for petroleum products in Ukraine is investigated. The dynamics of prices for petroleum products in Europe is analyzed. The tendencies of oil extraction in Ukraine are investigated and their steady decline in recent years has been determined. As a result of the analysis of the national market of crude oil, it was determined that: the tendency of crude oil trade in the Ukrainian market has been caused by the reduction of oil processing volumes, which, in turn, is caused by the exclusion from the domestic market of domestic fuel imports; the main reason for the unsatisfactory competitiveness of domestic motor fuel is its quality, which does not meet the requirements of modern standards and the price not corresponding to it; low quality motor fuel of domestic production is determined by the prevailing use for its production of low-quality (high-sulfur) import (Russian) oil; in general, the competitiveness of the domestic oil refining industry is considered low. Keywords. Oil, petroleum products, price, import, esport, market, dynamics.